SYNTHESIS OF MAGNETITE (Fe3O4) - GRAPHENE (GP) NANOCOMPOSITE BY SONOCHEMICAL METHOD AND ITS APPLICATION FOR ELECTROCHEMICAL BIOSENSOR'S ACTIVE MATERIAL BASED ON IMMUNOASSAY - NURLINA SUHANTO (NIM: 23315307), RHESTI
Early detection is an important step in preventing the spread of diseases. Biosensors offer a simpler, faster, and more accurate detection method of diseases than conventional laboratory methods. In this study, magnetite (Fe3O4) was composite with graphene platelet (GP) and used as a prostate specific antigen (PSA) detection biosensor material by electrochemical principle. The choice of Fe3O4 is based on its biocompatible and non-toxicity properties, also it known to be very effective in immobilizing biomolecules. Graphene has a large specific surface area, so it can absorb a number of biomolecules and become the site of Fe3O4 growth, thereby reducing the aggregation of Fe3O4 nanoparticles. In addition, graphene has a high electrical conductivity, which is useful for increasing electrochemical currents of biosensors. Several nanocomposite samples were successfully synthesized using sonochemical method at room temperature by varying the concentration ratio of GP and Fe3O4. The use of ultrasonic waves is one way to prevent agglomeration of Fe3O4 particles, so it resulting smaller particle size of Fe3O4. FeCl2.4H2O and FeCl3.6H2O are used as precursors to form Fe3O4 nanoparticles. The resulting nanocomposite has good crystallinity and purity with Fe3O4 nanoparticles attached to the GP surface. The greater concentration of Fe3O4, the greater the number and size of the resulting Fe3O4 nanoparticles, so that the XRD diffraction of Fe3O4 more clearly detected, covering of the GP diffraction. The measurements of the vibrating sample magnetometer (VSM) show that the nanocomposite has superparamagnetic properties shown with coercivity magnetic close to zero. The greater GP concentration, the magnetization saturation value (Ms) and remanen (Mr) are smaller indicating the decreasing properties of magnetism of the material. Small Ms value also show smaller size of Fe3O4 particles. The carbon paste electrode (EPK) made by mixing graphite and paraffin, is selected as a working electrode whose surface will be modified with a nanocomposite. Electrochemical properties were tested using cyclic voltammetry (CV) with K3[Fe(CN)6]/K4[Fe(CN)6] solution as the supporting electrolyte. The measurement iv results show the reduction and oxidation curve cycles of [Fe(CN)6]3-/4- and show that the nanocomposite can be a good electron transfer medium between the electrode surface and the electrolyte solution. This is evident from the increased peaks of oxidation (Ipa) and reduction (Ipc) current, and the closer of the redox peak (ΔEp). In addition, when compared with EPK alone, the effective surface area of the electrode (A) also increased. Thus, it can be said that the nanocomposite has better electrochemical catalytic properties than only EPK and EPKs that have been surface modified by only Fe3O4 or GP. G1F3 sample nanocomposite show the most optimum performance during electrochemical testing. This sample can increase the oxidation and reduction current of [Fe(CN)6]3-/4- up to 232 % and 702 % with A = 0.088 cm2. PSA is a biomarker that indicates an abnormality in the prostate gland (prostate cancer). To be able to recognize PSA, anti-PSA was immobilized on a G1F3 sample. Anti-PSA is covalently bonded to nanocomposites using NHS/EDC. To ensure the anti-PSA is tied to the nanocomposite, nanocomposites before and after immobilized anti-PSA are tested by fourier transformed infrared (FTIR). The FTIR spectrum results shown that the anti-PSA is bonded to the nanocomposite. In addition, the redox current of the anti-PSA/G1F3/EPK electrode has decreased. It also indicates that anti-PSA has been bound to the nanocomposite, so it can inhibit electron transfer. Once the anti-PSA is immobilized to the nanocomposite, the biosensor is tested to detect PSA. PSA and anti-PSA interactions increased with increasing PSA concentrations from 1 - 150 ng.mL-1 with a limit of detection (LOD) is 0.38 ng.mL-1. Biosensor showed a response to their specific antigen and has good stability, so it is very promising to be applied as an alternative material to early detection of cancer markers.